Martin Buber's spirituality Hasidic wisdom for everyday life - Kramer, Kenneth, 1941- (Lanham : Rowman & Littlefield Publishers, 2011)
.Cs7CED571B{text-align:left;text-indent:0pt;padding:0pt 0pt 0pt 0pt;margin:0pt 0pt 0pt 0pt}.cs5EFED22F{color:#000000;background-color:transparent;font-family:Times New Roman; font-size:12pt; font-weight:normal; font-style:normal; }.cs36E2AA4C{color:#000000;background-color:transparent;font-family:Times New Roman; font-size:8pt; font-weight:normal; font-style:normal; }This book explores how Martin Buber, one of the 20th century & rsquo;s great religious thinkers, answers the question of how to find meaning in life. The author explains Buber & rsquo;s Hasidic spirituality & mdash;a living connection b.
Cover; Half Title; Title; Copyright; Dedication; Dedication; Contents; Foreword By Maurice Friedman; Acknowledgments; Preface; Introduction Buber's Hasidic Spirituality; Part I Preliminary Practices; Chapter 1 Heart-Searching; Chapter 2 Your Particular Way; Chapter 3 Resolution; Part II Practicing Presentness; Chapter 4 Beginning with Yourself; Chapter 5 Turning toward Others; Chapter 6 Here Where You Stand; Conclusion Practicing Buber's Secret; Appendix Dialogue Journal; Glossary of Key Terms; Notes; Index.
Description based on print version record.
Keywords: Buber, Martin, 1878-1965.; Hasidim -- Quotations.$; Hasidism -- Quotations, maxims, etc; Spiritual life -- Judaism; Religion; RELIGION / Judaism / Rituals & Practice; Spiritual life -- Judaism; Hasidim -- Quotations; Hasidism -- Quotations, maxims, etc; Buber, Martin, -- 1878-1965.; Electronic books